2017
DOI: 10.1155/2017/8612819
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Investigation of Electrospun PLA Materials with Propolis Extracts and Silver Nanoparticles for Biomedical Applications

Abstract: An electrospun hydrophilic non-water-soluble biocompatible polylactic acid (PLA) nonwoven material was used as a delivery system for propolis ethanolic extract (PEE) and silver nanoparticles (AgNPs) that are known for their established antiseptic and antimicrobial activity. Combination of PEE and AgNPs in a single product should provide efficient antimicrobial protection and improved wound healing. Evaluations of PEE and AgNPs on morphology of electrospun materials, release kinetics of AgNPs and phenolic compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…To obtain the nonwoven mat, 22 ml of the solution is dosed at a rate of 1.5 ml/h [ 26 ]. Nonwoven wound dressings containing propolis [ 4 ] have been made with an electrospinning method using poly(lactide-co-glycolide) containing: 85 mole-% of lactidyl and 15 mole-% of glycolidyl comonomer units (PLGA 85 : 15) [ 24 , 27 ]. A solution of propolis is introduced to the polymer solution and mixed until a homogeneous mixture is obtained.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain the nonwoven mat, 22 ml of the solution is dosed at a rate of 1.5 ml/h [ 26 ]. Nonwoven wound dressings containing propolis [ 4 ] have been made with an electrospinning method using poly(lactide-co-glycolide) containing: 85 mole-% of lactidyl and 15 mole-% of glycolidyl comonomer units (PLGA 85 : 15) [ 24 , 27 ]. A solution of propolis is introduced to the polymer solution and mixed until a homogeneous mixture is obtained.…”
Section: Methodsmentioning
confidence: 99%
“…The difference lies in the character of polymer that is used to make the nonwovens. Studies performed by Kim et al [36], Adomavičūtė et al [14] and Sutjarittangtham et al [37] proved that the type of polymers from which the dressing are made is of key importance in changing the release profile of the drug. Results of their studies also confirmed that propolis is released slower from the PLA and PU nonwoven than from polymers with greater hydrophobicity.…”
Section: Discussionmentioning
confidence: 99%
“…By using this technique, it is possible to control the pharmacokinetic processes in such a way as to obtain a prolonged action of the active ingredient within the wound healing. These types of dressings are characterized by a number of beneficial properties, such as a large surface area and porous structure, better gas exchange and more effective absorption of exudate, protection against infections and dehydration, as well as the ease of introducing the active substance [1][2][3][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations